Dynamics of Colon Monocyte and Macrophage Activation During Colitis - Jones, Gareth-Rhys; Bain, Calum C.; Fenton, Thomas M.; Kelly, Aoife; Brown, Sheila L.; Ivens, Alasdair C.; Travis, Mark A.; Cook, Peter C.; MacDonald, Andrew S. (Frontiers in Immunology, 2018)
Background Macrophages are pivotal in coordinating a range of important processes in the intestines, including controlling intracellular infections and limiting damaging inflammation against the microbiota. However, it is unclear how gut macrophages, relative to recruited blood monocytes and other myeloid cells contribute to the intestinal inflammatory milieu nor how macrophages and their monocyte precursors mediate recruitment of other immune cells to the inflamed intestine. Methods Myeloid cell populations isolated from colonic IBD or murine dextran sulphate sodium (DSS) induced colitis were assessed using flow cytometry and compared to healthy controls. In addition, mRNA expression profiles in human and murine colon samples, and in macrophages and monocytes from healthy and inflamed murine colons, were analysed by quantitative PCR (qPCR) and mRNA microarray. Results We show that the macrophage:monocyte balance is disrupted in colon inflammation to favour recruitment of CD14+HLA-DRInt cells in humans, and Ly6CHi monocytes in mice. In addition, we identify that murine blood monocytes receive systemic signals enabling increased release of IL-1β prior to egress from the blood into the colon. Further, once within the colon and relative to other myeloid cells, monocytes represent the dominant local sources of both IL-1β and TNF. Finally, our data reveal that, independent of inflammation, murine colon macrophages act as major sources of Ccl7 and Ccl8 mRNA, chemokines that trigger further recruitment of their pro-inflammatory monocyte precursors. Conclusions Our work suggests that strategies targeting macrophage-mediated monocyte recruitment may represent a promising approach for limiting the chronic inflammation that characterises IBD.